A revision of five genera of Alysiini (Hymenoptera, Braconidae, Alysiinae) from China, with description of five new species - Zhu, Jiachen; Achterberg, Cornelis Van; Chen, Xuexin (Zootaxa, 2025)
Five genera of Alysiini (Alysiinae, Braconidae) from China are reviewed. Five new species are described and illustrated, i.e., Anisocyrta parallela sp. nov., A. rugosa sp. nov., Trachyusa punctata sp. nov., T. microporosa sp. nov. and Separatatus platystigma sp. nov. Seven species are newly recorded from China: Adelurola florimela (Haliday, 1838), Anisocyrta perdita Haliday, 1838; Pentapleura savva Belokobylskij, 1998; P. atlasovi Belokobylskij, 1998; P. angustula (Haliday, 1838); P. fuliginosa (Haliday, 1838); and Trachyusa vasilisk Belokobylskij, 1998. Keys to the species of Anisocyrta Foerster, Pentapleura Foerster, and Separatatus Chen & Wu are provided.